Parametric study on thermodynamic performance of a novel PV panel and thermal hybrid solar system. (5th November 2020) - Wang, Gang; Wang, Botong; Yao, Yubo; Lin, Jianqing; Chen, Zeshao; Hu, Peng
Highlights: A novel hybrid solar PV panel and thermal (PVPT) system is proposed. A new spectral beam splitter is designed for the PVPT system. Parametric study on thermodynamic behavior of the PVPT system is conducted. Abstract: The current study presents a novel hybrid solar multi-segment photovoltaic panel/thermal (PVPT) system. The design principle of the PVPT system is introduced. The arranged optical filters are employed as the concentrator for the solar receiver tube in this PVPT system. A new optical filter design is conducted. The optical behaviour evaluation of the PVPT system is launched and the results demonstrate that with the receiver height increased, an optimal receiver height exists, leading to the highest energy flux on the thermal receiver. Under a typical fixed parameter condition, the total output power of the PVPT system is 2078.3 W. The thermodynamic performance evaluation results of the PVPT system demonstrate that with the solar irradiance increased, the total output power and overall energy efficiency of the PVPT system both increase. The increase of PV cell temperature can result in the decreases of the output power and energy efficiency of the PVPT system. As the operating temperature of the solar receiver tube increases, the output power of the PVPT system has the peak value. An optimal receiver tube temperature exists, leading to the maximum output power.